2017
DOI: 10.1039/c7dt03226a
|View full text |Cite
|
Sign up to set email alerts
|

Allowing the direct interaction of N-aryl α-diimines with a high valent metal chloride: one-pot WCl6-promoted formation of quinoxalinium salts

Abstract: The full potential of a high valent metal chloride as both a chlorinating and an oxidative agent was explored by allowing WCl to react with N-(2,6-diisopropylphenyl) α-diimines, in CHCl at room temperature. These α-diimines underwent unprecedented conversion to quinoxalinium cations via intramolecular C-N coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…In the framework of our research on the coordination chemistry of α-diimines, [18][19][20][21] and in their derivatization with bioactive groups via esterification reactions, [22,23] we became interested in obtaining the α-diimine compound D1 bearing two 4-cyclohexanecarboxylic acid groups as nitrogen substituents. Using the classical procedure (see Scheme 1A), (1S,4S)-4-aminocyclohexanecarboxylic acid and glyoxal were refluxed in methanol in the presence of a catalytic amount of acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In the framework of our research on the coordination chemistry of α-diimines, [18][19][20][21] and in their derivatization with bioactive groups via esterification reactions, [22,23] we became interested in obtaining the α-diimine compound D1 bearing two 4-cyclohexanecarboxylic acid groups as nitrogen substituents. Using the classical procedure (see Scheme 1A), (1S,4S)-4-aminocyclohexanecarboxylic acid and glyoxal were refluxed in methanol in the presence of a catalytic amount of acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…20 The unclean NbCl 5 directed activation of DAD Dip produces, among the other products, the quinoxalinium salt 2 and, in this respect, matches the outcome of the reaction with WCl 6 . 25 The formation of 2 from DAD Dip presumably takes place via DAD Dip to Nb electron transfer, and release of one isopropyl group. The latter was detected by GC-MS as isopropyl chloride in the final reaction mixture; on the other hand, a variable temperature EPR study suggested the presence of minor amounts of the isopropyl radical, .…”
Section: Resultsmentioning
confidence: 99%
“…12,13,14,24 The first direct interaction (i.e., in the absence of further reactants) of α-diimines with a HVM halide (WCl 6 ) was recently reported by us, allowing the unusual conversion of the organic substrate into quinoxalinium cations (Scheme 1). 25 Scheme 1. WCl 6 -mediated conversion of α-diimine to quinoxalinium.…”
mentioning
confidence: 99%
“…In particular, WCl 6 exhibits relatively weak W−Cl bonds, allowing the stoichiometric modification of simple molecules through unconventional pathways. Examples include the transformation of imines into aza‐2‐allenium and nitriulium cations, the former being generated via unusual N 2 elimination, and of α‐diimines into quinoxalinium salts . Also niobium pentahalides have been found to provide unique reactivity patterns to organic species,,, and their chemistry has witnessed a significant advance in the last years,, encouraged by their cheapness and the substantial non‐toxicity of the element niobium .…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the transformation of imines into aza-2-allenium and nitriulium cations, [9] the former being generated via unusual N 2 elimination, and of α-diimines into quinoxalinium salts. [10] Also niobium pentahalides have been found to provide unique reactivity patterns to organic species, [1c,7,11] and their chemistry has witnessed a significant advance in the last years, [7,12] encouraged by their cheapness and the substantial non-toxicity of the element niobium. [13] Compared to WCl 6 , NbX 5 (X = F, Cl) are more inert to reduction processes, and comprise relatively strong niobium-halide bonds, [8] thus disfavouring halide/oxygen exchange reactions.…”
Section: Introductionmentioning
confidence: 99%